Emerging noninvasive methylation biomarkers of cancer prognosis and drug response prediction. (August 2022) - Oliver, Javier; Garcia-Aranda, Marilina; Chaves, Patricia; Alba, Emilio; Cobo-Dols, Manuel; Onieva, Juan Luis; Barragan, Isabel
Abstract: Cancer is the second leading cause of death worldwide being responsible for 9.6 million deaths in 2018. Epigenetic alterations are key in directing the aberrant expression of tumor-associated genes that drive cellular malignant transformation and cancer progression. Among epigenetic alterations, DNA methylation is the most deeply studied one in relation to environmental exposure. Tissue biopsies have traditionally been the main procedure by which a small sample of body tissue is excised to confirm cancer diagnosis or to indicate the primary site when cancer has spread. In contrast, the analysis of circulating tumor-derived material, or tumor circulome, by means of liquid biopsy of peripheral blood, urine, saliva or sputum is a noninvasive, fast and reproducible alternative to tissue biopsy. Recently, the assessment of epigenetic alterations such as DNA methylation and hydroxymethylation in circulating free DNA has been proved possible. These marks can be associated to prognosis and response to a variety of treatments including chemotherapy, hormonotherapy or immunotherapy. Epigenetic biomarkers may offer some advantages over RNA or genetic biomarkers given their stability in bodily fluids and their high tissue-specificity. While many challenges are still ahead, the unique advantages of these types of biomarkers is urging the scientific community to persevere in their clinical validation and integration into reliable prediction models. This review aims at recapitulating the emerging noninvasive DNA methylated biomarkers of importance for prediction of prognosis and drug response in cancer.